Recent updates in nanotechnological advances for wound healing: A narrative review - Hitesh Chopra; Yugal Kishore Mohanta; Saurov Mahanta; Tapan Kumar Mohanta; Inderbir Singh; Satya Kumar Avula; Sarada Prasanna Mallick; Ali A. Rabaan; Hajir AlSaihati; Ahmed Alsayyah; Mohammed Alissa; Hussain R. Alturaifi; et al. (2023)
Abstract The repair and remodeling of injured tissues, known as wound healing, is a multifaceted process. The use of nanotechnology to speed up the healing process of wounds by promoting the right kind of mobility through different mechanisms has shown a lot of promise. Several nanotechnologies with novel properties have emerged in recent years, each of which targets a different issue associated with wound-healing processes. Through their antibacterial, anti-inflammatory, and angiogenic actions, nanomaterials may alter the wound microenvironment from a non-healing to a healing state. Wound dressings including hydrogels, gelatin sponges, films, and bandages may all benefit from the use of nanoparticles (NPs) to keep harmful microbes out. The addition of bioactive substances like antibiotics, NPs, and growth factors to certain dressings may further boost their efficacy. In conclusion, this review sheds light on wound healing that may be aided by the special features of materials based on nanotechnology. Although nanomaterials for wound healing show great promise, further study is needed before this promising area can convert its findings into consumer-friendly solutions.